Fat distribution and ectopic lipid deposition in morbidly obese pregnant women in the third trimester: MRI analyses. (18th April 2012) - Barr, SM; Chiswick, C; Semple, S; Gray, C; Cooper, A; Forbes, S; Morton, NM; Walker, BR; Norman, JE
Abstract : Maternal obesity is increasingly prevalent in the UK and is associated with a significant increase in maternal and fetal morbidity and mortality. In non-pregnant obese subjects, reduced capacity of adipose tissue for lipid storage and ectopic lipid deposition in liver and skeletal muscle contribute to insulin resistance. We hypothesised that morbid obesity is associated with enhanced ectopic lipid accumulation in the third trimester of pregnancy. Healthy lean (BMI<25kg/m2) and morbidly obese (BMI>40kg/m2) women were imaged at approximately 36 weeks gestation in a 3T MRI scanner (Siemens) (n=10/group). 1H-Magnetic Resonance Spectroscopy was carried out in the right quadriceps muscle using a voxel size of 2cm3 and lipid concentration was calculated from the water-suppressed acquisition using the spectroscopy analysis tool JMRUI. Intrahepatic lipid signal contribution was calculated through subtraction of in and out of phase images. Adipose tissue distribution was quantified using a semi-automated thresholding technique (SliceOMatic). Hepatic lipid content was low in obese pregnant women with similar levels in lean and obese pregnant women at 36 weeks gestation (1.6±0.35 vs 1.2±0.3%). Subcutaneous adipose tissue was the largest abdominal adipose tissue depot in lean and obese women. Obese women had significantly greater subcutaneous (2.3 vs 0.5kg, p<0.0001) and intra-abdominal (0.5 vs 0.1kg, p<0.0001) lipid deposits compared with lean women. We conclude that obesity is not associated with elevated hepatic lipid accumulation in the third trimester of pregnancy, in contrast to weight matched, non pregnant individuals, and that this points to a potential hepato-protective mechanism from obesity in pregnancy.